PENGARUH DEBT DEFAULT, KUALITAS AUDITOR, OPINI AUDIT TAHUN SEBELUMNYA, KONDISI KEUANGAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEMUNGKINAN PENERIMAAN OPINI AUDIT GOING CONCERN - Lois Fransnawati Stefanus, 07.05.52.0151; Nurhayati, Ida (Students Journal of Accounting and Banking, 2013)
The purpose of this research is to give empirical prove about audit quality, company financial condition, opinion towards the previous year, company growth and debt default towards the receiving opinion of audit going concern. Audit going concern opinion is important information for invertors related to the company ability in maintaining business activity. Sample for this research is a manufacture which has been registered in Indonesia stock Exchange for 2008-2011 including 56 companies. The receiving of audit going concern opinion is dummy variable whose value 1 for a company which receives audit opinion of non going concern. The result of research reveals that variable debt default, auditor quality have positive side but not significant influence towards the opinion receiving of audit going concern. And previous year audit opinion, company financial condition (profitability and liquidity) and company growth have negative side and not significant influence towards the opinion receiving of audit going concern this term is revealed by recreation value (Î²) and significant value (Î±).Keywoords: Going concern, audit quality, company financial condition, precious year, audit opinion, company growth, debt default